Physical activity volume and intensity distribution in relation to bone, lean and fat mass in children. (17th November 2022) - Skinner, Annie M.; Vlachopoulos, Dimitris; Barker, Alan R.; Moore, Sarah A.; Rowlands, Alex V.; Soininen, Sonja; Haapala, Eero A.; Väistö, Juuso; Westgate, Kate; Brage, Soren; Lakka, Timo A.
Abstract : Considering physical activity (PA) volume and intensity may provide novel insights into the relationships of PA with bone, lean, and fat mass. This study aimed to assess the associations of PA volume, PA intensity distribution, including moderate‐to‐vigorous PA (MVPA) with total‐body‐less‐head bone mineral content (BMC), lean, and fat mass in children. A population sample of 290 Finnish children (158 females) aged 9–11 years from the Physical Activity and Nutrition in Children (PANIC) Study was studied. PA, including MVPA, was assessed with a combined heart rate and movement sensor, and the uniaxial acceleration was used to calculate average‐acceleration (a proxy metric for PA volume) and intensity‐gradient (reflective of PA intensity distribution). Linear regression analyzed the associations of PA volume, PA intensity and MVPA with BMC, lean mass, and fat mass assessed by dual‐energy X‐ray absorptiometry. PA volume was positively associated with BMC in females (unstandardised regression coefficient [ ß ] = 0.26) and males ( ß = 0.47), and positively associated with lean ( ß = 7.33) and negatively associated with fat mass in males ( ß = −20.62). PA intensity was negatively associated with BMC in males ( ß = −0.13). MVPA was positively associated with lean mass in females and males ( ß = 0.007 to 0.012), and negatively associated with fat mass in females and males ( ß = −0.030 to −0.029). PA volume may be important for improving BMC in females and males, and increasing lean and reducing fat mass in males, whereas MVPA may be important for favorable lean and fat outcomes in both sexes.